Surgically curable Pancreas Enigma: Solid Pseudopapillary Tumor. Report of a case and literature review - Kurşat Rahmi Serin; Muharrem Oner; Nadir Adnan Hacım (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Solid pseudopapillary tumor (SPT) is a rare pancreatic neoplasm, classified as low-grade malignant tumor by the World Health Organization in 2000. Surgical treatment usually provide curative intent. Here in we report a 30 years-old woman whom had been operated upon possible benign pancreatic head mass diagnosed histopathologically as solid pseudopapillary tumor. And we aimed to review the literature on the basis of the case. In conclusion, solid pseudopapillary tumors are slow-growing tumors, with unpredictable potential for malignancy. Aggressive surgery yields favorable results even in the presence of vascular invasion and metastatic disease.